(untitled) (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2023)
The general objective of this research is to enhance the maturation processes of gross motor skills in boys and girls of the second grade of Colegio Estrella del Sur IED, using gamification as a didactic strategy. The study involved students from the 201st grade, 6 boys and 4 girls, their ages range between 7 and 8 years old. The research uses a mixed methodology, the instruments used in this study were the observation card, a structure that allows observing and analyzing the reactions of the participating students to the dynamics established during the implementation of the didactic sequence. Another instrument used was the motor skills test for elementary school, applied at the beginning and at the end of the implementation of the didactic sequence to analyze the motor development of the children in an appropriate classroom environment. Finally, an evaluation matrix called LORI was also used, which contains clarity in nine items that are welcomed in the present research because it will facilitate the evaluation of the didactic strategy. The findings of this research were: the participants demonstrate skills for the use of technologies and the exploration of gestures necessary for the use of video games. Additionally, it was possible to perceive the level of interest presented by the group, the ability to listen improved, the gamification in the learning process improved, and the use of video games in the learning process improved.